Pengembangan Buku Saku Aksi Mitigasi Perubahan Iklim melalui Pengelolaan Sampah untuk Membangun Ketahanan Keluarga - Oktarianto, Muhammad Fazrin; Nugraheni, Prastiti L; Mashabi, Nurlaila A; Zulfa, Vania; Kabbaro, Hurriyyatun (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2022)
Oktarianto MF, Nugraheni PL, Mashabi NA, Zulfa V, Kabbaro H. 2022. Development of a Pocket Book of Climate Change Mitigation Action through Waste Management to Build Family Resilience. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 974-982. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Plastic waste is one source of greenhouse gas emissions that affect climate change. The purpose of this study is to develop a pocket book for climate change mitigation actions through waste management to build family resilience as a guide or reference in waste management. This study uses research and development methods with the ADDIE model but only until the Development stage. The development of this pocket book media was carried out through a feasibility test of 2 material experts, a media expert and a small group test of 13 respondents. The results of the feasibility category from the pocket book feasibility test obtained the Eligible category by 2 material experts with a score of 80% material experts 1 and 79,5% material experts 2, the Very Eligible category by media expert with a score of 100% and Very Eligible by respondents with a score of 88%. The results can state that the pocket book of climate change mitigation actions through waste management to build family resilience is feasible to use. Researchers hope that this pocket book can be used as a guide or reference in waste management as a form of climate change mitigation action and build family resilience.